Implementing the Scrum Method for Developing a Population Information System - Wahyu Setyaningsih, Putry; Witanti, Arita; Widatama, Krisna (Jurnal Sistem Cerdas, 2025)
The adoption of Population Information System is crucial to enhance work effectiveness and serves as a manifestation of transparency in population data management. The complexity from design to implementation of such a population information system poses its own challenges. There are at least three main issues in system design, namely time estimation, team management, and ensuring the quality of system being developed. These issues must be addressed early on to prevent potential team management problems during the design and development stages of the application. One suitable method that can be employed for the design of the population information system is the Scrum methodology. Scrum is a software development framework that emphasizes a collaborative and adaptive approach. It falls under the Agile methodology, aiming to produce products that are more responsive to changes and enabling teams to adapt quickly in a dynamic environment. Scrum also promotes transparency in the development process, aiding in monitoring system progress and information accuracy. Through the implementation of the Scrum methodology, it is expected that the design of the Population Information System can be well-managed, preventing the issues mentioned earlier. Moreover, the application of the Scrum methodology in designing the population information system is a tangible step in the implementation of large-scale application development projects. It is envisioned that Scrum could replace the traditional Waterfall methodology, which has been commonly used until now.